REVIEW OF CLINICAL SYNDROMES IN COVID-19 IN GLOBAL PERSPECTIVE: A STEP TOWARDS INFECTION PREVENTION CONTROL IN FORENSIC PRACTICES - Parekh, Utsav; Gupta, Sanjay; Johnson, Abraham (Journal of Forensic Medicine and Toxicology, 2020)
The coronaviruses are a large family comprises of various single stranded RNA (+ssRNA) viruses that can be isolated in different species, some causing human illness including Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS) and others that can cross species barriers and circulate among animals, including camels, cats and bats.1 The 2019 novel coronavirus (2019-nCoV) or the severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) as it is now called, is rapidly spreading from its origin in Wuhan City of Hubei Province of China to the rest of the world.2,3 Johns Hopkins University and other forums provides the constantly changing case detection rate on daily basis.4 The future course of this virus is not known till date.
Keywords: EPIDEMIOLOGY; animals; corona virus